2009
DOI: 10.3748/wjg.15.3232
|View full text |Cite
|
Sign up to set email alerts
|

Cystic echinococcosis of the liver and lung treated by radiofrequency thermal ablation: An ex-vivo pilot experimental study in animal models

Abstract: RTA appears to be very effective in killing hydatid cysts of explanted liver and lung. Bile duct and bronchial wall necrosis, persistence of endocyst attached to pericystium, should help avoid or greatly decrease in vivo post-treatment fistula occurrence and consequent overlapping complications that are common after surgery or percutaneous aspiration, injection and reaspiration. In vivo studies are required to confirm and validate this new therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…Less explored techniques, such as RFA, may also be further evaluated for the treatment of complex hepatic cysts. However, pre-clinical studies, such as that conducted by Lamonaca and colleagues [ 50 ], should be performed, with special focus on the treatment of complex hepatic cysts. In any case, all percutaneous techniques are invasive, with different levels of complexity, and the need for the development of alternative treatments applicable in remote, resource-poor areas remains urgent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less explored techniques, such as RFA, may also be further evaluated for the treatment of complex hepatic cysts. However, pre-clinical studies, such as that conducted by Lamonaca and colleagues [ 50 ], should be performed, with special focus on the treatment of complex hepatic cysts. In any case, all percutaneous techniques are invasive, with different levels of complexity, and the need for the development of alternative treatments applicable in remote, resource-poor areas remains urgent.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, no preliminary in vitro or ex vivo / in vivo animal studies had been conducted before the application of this technique in human CE. Only a later study performed in 2009 on CE cysts excised from sheep liver and lung confirmed the efficacy of the procedure on isolated cysts [ 50 ]; however, to our knowledge an in vivo experiment on E. granulosus -infected animals has never been performed.…”
Section: Non-conventional Treatmentsmentioning
confidence: 99%
“…Postoperative complications include biliary leakage, fistulas, and liver abscess formation. 13 Lamonaca et al 14 concluded that in RFA treatment, bile duct and bronchial wall necrosis and persistence of endocyst attached to pericystium may be associated with decreased posttreatment fistula occurrence and consequent overlapping complications that are common after surgery, percutaneous aspiration, injection, and reaspiration. 14 Furthermore, biliocystic communication and cystocutaneous fistula with bile leakage after surgery can be treated by ablation of cysts with fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…But now there are lots of problems existed in ablation equipment temperature and power control, which directly affect the melting effect. So this paper is based on this target to design a more effective radiofrequency ablation temperature and power control system, measuring temperature ablation area center and edge at the same time [5]. In terms of software algorithm design of the control system, much of them are based on fuzzy control algorithm [6,7], neural network algorithm and genetic algorithm, and the PID algorithm design [8][9][10][11].…”
Section: Radiofrequency Ablation System and Temperature Control Modulementioning
confidence: 99%